Dynamic transcriptome profiling towards understanding the morphogenesis and development of diverse feather in domestic duck - Jing Yang (BMC Genomics, 2018)
Abstract Background Feathers with complex and fine structure are hallmark avian integument appendages, which have contributed significantly to the survival and breeding for birds. Here, we aimed to explore the differentiation, morphogenesis and development of diverse feathers in the domestic duck. Results Transcriptome profiles of skin owing feather follicle from two body parts at three physiological stages were constructed to understand the molecular network and excavate the candidate genes associated with the development of plumulaceous and flight feather structures. The venn analysis of differentially expressed genes (DEGs) between abdomen and wing skin tissues at three developmental stages showed that 38 genes owing identical differentially expression pattern. Together, our data suggest that feather morphological and structural diversity can be possibly related to the homeobox proteins. The key series-clusters, many candidate biological processes and genes were identified for the morphogenesis, growth and development of two feather types. Through comparing the results of developmental transcriptomes from plumulaceous and flight feather, we found that DEGs belonging to the family of WNT, FGF and BMP have certain differences; even the consistent DEGs of skin and feather follicle transcriptomes from abdomen and wing have the different expression patterns. Conclusions Overall, this study detected many functional genes and showed differences in the molecular mechanisms of diverse feather developments. The findings in WNT, FGF and BMP, which were consistent with biological experiments, showed more possible complex modulations. A correlative role of HOX genes was also suggested but future biological verification experiments are required. This work provided valuable information for subsequent research on the morphogenesis of feathers.